2017
DOI: 10.1002/fuce.201600222
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Ni Particle Shape Change and Ni Migration in Ni–YSZ Electrodes – a Hypothesis

Abstract: This paper deals with degradation mechanisms of Ni-YSZ electrodes for solid oxide cells, mainly solid oxide electrolysis cells (SOECs), but also to some extent solid oxide fuel cells (SOFCs). Analysis of literature data reveals that several apparently different and even in one case apparently contradicting degradation phenomena are a consequence of interplay between loss of contact between the Ni-YSZ (and Ni-Ni particles) in the active fine-structured composite fuel electrode layer and migration of Ni via weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
124
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 126 publications
(142 citation statements)
references
References 26 publications
17
124
0
1
Order By: Relevance
“…At the inlet of the tested cell, enrichment of Ni in the support layer just next to the active electrode is clearly visible, while at the outlet of the tested cell and in the reference cell, the Ni distribution is rather homogeneous. A more detailed discussion on the Ni migration can be found in [30]. Such phenomenon was however not found in the present test as confirmed by high resolution BSE images (not shown here).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…At the inlet of the tested cell, enrichment of Ni in the support layer just next to the active electrode is clearly visible, while at the outlet of the tested cell and in the reference cell, the Ni distribution is rather homogeneous. A more detailed discussion on the Ni migration can be found in [30]. Such phenomenon was however not found in the present test as confirmed by high resolution BSE images (not shown here).…”
Section: Discussionsupporting
confidence: 66%
“…It has been reported that kinetics for H 2 or CO oxidization are slightly faster than for H 2 O or CO 2 reduction [13,14]. At the Ni-YSZ electrode, beside loss of contact between Ni and Ni grain due to Ni agglomeration or Ni migration [19,20,28], nano ZrO 2 precipitation from Zr dissolved in the Ni bulk was observed [29,30]. In SOFC mode the process is highly exothermic, while in SOEC mode it is dependent on the operation voltage whether heat is produced or consumed in the electrolysis overall process (considering both reaction entropy changes and joule heat).…”
Section: Introductionmentioning
confidence: 97%
“…19, 26 The thickness of this layer is also increasing in the direction of the fuel inlet. In particular, at the fuel inlet the thickness of the layer is doubled.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of percolation indicated the Nickel migration from the active layer to the support. Hence, it was also of interest to investigate the theory of Nickel migration . For this purpose, line scans were done through Cell‐C to check for the possibility of loss in Ni surface area due to migration.…”
Section: Resultsmentioning
confidence: 99%
“…For further information, please refer to Appendix‐B. This methodology gives an indication of the magnitude of the Ni migration from the active region to the fuel support .…”
Section: Resultsmentioning
confidence: 99%